Allogeneic DNT cell therapy synergizes with T cells to promote anti-leukemic activities while suppressing GvHD - Jongbok Lee; Hyeonjeong Kang; Branson Chen; Yoosu Na; Ismat Khatri; Fraser Soares; Housheng Hansen He; Arjun D. Law; Tianzhong Pan; Armin Gerbitz; Xiaoyu Zhu; Mark D. Minden; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a second-line treatment with curative potential for leukemia patients. However, the prognosis of allo-HSCT patients with disease relapse or graft-versus-host disease (GvHD) is poor. CD4+ or CD8+ conventional T (Tconv) cells are critically involved in mediating anti-leukemic immune responses to prevent relapse and detrimental GvHD. Hence, treatment for one increases the risk of the other. Thus, therapeutic strategies that can address relapse and GvHD are considered the Holy Grail of allo-HSCT. CD3+CD4−CD8− double-negative T cells (DNTs) are unconventional mature T cells with potent anti-leukemia effects with “off-the-shelf” potential. A phase I clinical trial demonstrated the feasibility, safety, and potential efficacy of allogeneic DNT therapy for patients with relapsing acute myeloid leukemia (AML) post-allo-HSCT. Here, we studied the impact of DNTs on the anti-leukemic and GvHD-inducing activities of Tconv cells. DNTs synergized with Tconv cells to mediate superior anti-leukemic activity. Mechanistically, DNTs released soluble factors which activated and evoked potent anti-leukemic activities of Tconv cells. In contrast, DNTs suppressed GvHD-inducing activities of Tconv cells in a CD18-dependent manner by mediating cytotoxicity against proliferative Tconv cells. The seemingly opposite immunological activities of DNTs were dictated by the presence or absence of AML cells. Collectively, these results support the potential of DNTs as an adjuvant to allo-HSCT to address both disease relapse and GvHD.